Pravastatin for early‐onset pre‐eclampsia: a randomised, blinded, placebo‐controlled trial. (14th December 2019) - Ahmed, A; Williams, DJ; Cheed, V; Middleton, LJ; Ahmad, S; Wang, K; Vince, AT; Hewett, P; Spencer, K; Khan, KS; Daniels, JP; ,
Summary: Objective: Women with pre‐eclampsia have elevated circulating levels of soluble fms‐like tyrosine kinase‐1 (sFlt‐1). Statins can reduce sFlt‐1 from cultured cells and improve pregnancy outcome in animals with a pre‐eclampsia‐like syndrome. We investigated the effect of pravastatin on plasma sFlt‐1 levels during pre‐eclampsia. Design: Blinded (clinician and participant), proof of principle, placebo‐controlled trial. Setting: Fifteen UK maternity units. Population: We used a minimisation algorithm to assign 62 women with early‐onset pre‐eclampsia (24 +0 –31 +6 weeks of gestation) to receive pravastatin 40 mg daily ( n = 30) or matched placebo ( n = 32), from randomisation to childbirth. Primary outcome: Difference in mean plasma sFlt‐1 levels over the first 3 days following randomisation. Results: The difference in the mean maternal plasma sFlt‐1 levels over the first 3 days after randomisation between the pravastatin ( n = 27) and placebo ( n = 29) groups was 292 pg/ml (95% CI −1175 to 592; P = 0.5), and over days 1–14 was 48 pg/ml (95% CI −1009 to 913; P = 0.9). Women who received pravastatin had a similar length of pregnancy following randomisation compared with those who received placebo (hazard ratio 0.84; 95% CI 0.50–1.40; P = 0.6). The median time from randomisation to childbirth was 9 days (interquartile range [IQR] 5–14 days) for the pravastatin group and 7 days (IQR 4–11 days) for the placebo group. There were three perinatal deaths in the placebo‐treated group and no deaths or serious adverse events attributable to pravastatin. Conclusions: We found no evidence that pravastatin lowered maternal plasma sFlt‐1 levels once early‐onset pre‐eclampsia had developed. Pravastatin appears to have no adverse perinatal effects. Tweetable abstract: Pravastatin does not improve maternal plasma sFlt‐1 or placental growth factor levels following a diagnosis of early preterm pre‐eclampsia #clinicaltrial finds. Tweetable abstract: Pravastatin does not improve maternal plasma sFlt‐1 or placental growth factor levels following a diagnosis of early preterm pre‐eclampsia #clinicaltrial finds.